Art et politique: nouvelles formes d'engagement artistique au Québec - Lamoureux, Ève (Collection Théorie, 2009)
Les artistes contemporains délaissent les grandes luttes communes, les partis politiques, et acceptent les subventions de l'État. Ils refusent les étiquettes et se moquent du mythe de l'artiste guidant le peuple. Quand l'oeuvre d'art devient fragments, mouvement, quand son sens est ouvert et dépend de l'expérience du spectateur, quelle est son action sur le monde? Peut-on encore croire à sa portée politique? Les nostalgiques pleurent la disparition de l'art engagé. Pour Ève Lamoureux, l'art engagé n'a jamais cédé; il résiste d'une autre manière, à un autre pouvoir, sur d'autres terrains. Exit la division entre l'art pour l'art et l'art au service d'une idée. Exit la conception avant-gardiste militante de l'art engagé. L'engagement actuel passe par une action micropolitique multiforme, une création soucieuse de l'Autre, à la fois autonome et collective, misant sur le processus et la participation. Ainsi, l'auteure nous montre de quelle façon l'art apporte une nouvelle définition de l'engagement politique. Cet essai analyse la démarche d'artistes québécois comme l'ATSA, BGL, Doyon/Demers, Danyèle Alain, Sylvie Cotton, Nicole Jolicoeur, Devora Neumark, Alain-Martin Richard, Jean-Claude St-Hilaire et Raphaëlle de Groot. En prolongeant, sur le plan théorique, des créations souvent performatives et éphémères (décors, manifestations, dialogues, oeuvres à compléter soi-même, etc.), ce livre les situe dans l'histoire récente de l'art et met en lumière leur dimension politique.
Keywords: 1900-1999; 2000 à aujourd'hui; amériques; approches et analyses; art engagé; arts; canada; cours; discipline; féminisme pop; har4600; histoire de l'art; histoire et politique; premier cycle; périodes historiques; québec; régions géographiques; science politique; science politique et droit; thématiques

Cyborgs et corps piratés dans la littérature de science-fiction - Bréan, Simon (Critique, 2008)
« 50 % homme, 50 % machine, 100 % flic ! » : Robocop est un policier torturé par des criminels et qui ne doit la vie qu’à des implants cybernétiques. Son exosquelette électronique en fait le meilleur policier des États-Unis : invulnérable, mais aussi précis, intègre, infaillible. Moins humain pourtant que le slogan ne pourrait le faire croire, Robocop se heurte à une directive secrète implantée dans son cerveau informatisé et l’empêchant d’arrêter un dirigeant corrompu de la société qui en a fait un cyborg. Privé de son libre-arbitre, l’homme cybernétique paie d’une partie de son humanité ses améliorations physiques. Robocop incarne les fantasmes ambivalents suscités par la cybernétique, à la fois promesse d’un dépassement de l’humanité à l’aide des machines et hantise d’un piratage du corps humain par la technologie. C’est à travers ce genre d’images frappantes que la science-fiction évoque de manière ludique les conséquences possibles de recherches scientifiques. Toutefois, le cyborg est moins une figure élaborée à partir de la cybernétique elle-même que l’incarnation d’un désir diffus, celui d’une participation de plus en plus intime de l’être humain aux progrès technologiques. La cybernétique comme discipline scientifique peut être définie comme la science des systèmes, dans la mesure où elle s’intéresse à la façon dont les parties d’un ensemble interagissent entre elles. L’analyse cybernétique s’applique aussi bien au corps humain qu’à une machine, même s’il n’existe entre les deux qu’un rapport d’homologie…
Keywords: approches et analyses; arts; cibernétique; corps; cours; discipline; féminisme pop; lit4700; premier cycle; ressource en ligne; sciences; technologie; thématiques; études littéraires

La transidentité: de l'espace médiatique à l'espace public - Espineira, Karine (Champs visuels, 2008)
C'est à partir de l'opération de Christine Jorgensen en 1952 au Danemark, que le fait qu'un homme puisse devenir une femme, après une intervention chirurgicale, entre dans l'esprit du grand public en raison de sa très forte médiatisation. Les identités trans' sont alors loin de s'affirmer comme telles. Il faudra attendre la fin des années 80 pour assister à l'émergence d'une visibilité prenant une forme revendicative. Entre les deux, la psychiatrisation de l'identité. Grâce à l'Internet, les transidentités ne sont plus isolées les unes des autres et ne rejouent plus la dramatique du changement de sexe comme une individuelle et éternelle première fois. Une mémoire s'élabore, se fixe et génère une culture. Leurs relations à l'information et l'identitaire questionnent tout autant. Cette recherche considère le groupe transidentitaire comme un monde social s'institutionnalisant dans un esprit multidisciplinaire à la lumière des sciences de l'information et de la communication, de la psychosociologie, de la théorie de l'engagement, de l'ethnométhodologie, de la sociologie de la traduction et de la communication instituante. L'analyse du traitement télévisuel de la transidentité, considérée comme expression la plus singulière de l'identité, est-elle susceptible de donner des outils de lectures sur la construction des normes de genre au-delà de la transidentité ?
Keywords: 1900-1999; 1950-1959; 1980-1989; 1990-1999; 2000 à aujourd'hui; 2000-2009; LGBTQIA2+; approches et analyses; cours; danemark; discipline; discours dominant; europe; féminisme pop; identités LGBTQIA2+; premier cycle; périodes historiques; queer; régions géographiques; sexualité; shm4000; systèmes d'oppressions; thématiques; transféminisme

Sex objects: art and the dialectics of desire - Doyle, Jennifer (University of Minnesota Press, 2006)
The declaration that a work of art is “about sex” is often announced to the public as a scandal after which there is nothing else to say about the work or the artist-controversy concludes a conversation when instead it should begin a new one. Moving beyond debates about pornography and censorship, Jennifer Doyle shows us that sex in art is as diverse as sex in everyday life: exciting, ordinary, emotional, traumatic, embarrassing, funny, even profoundly boring. Sex Objects examines the reception and frequent misunderstanding of highly sexualized images, words, and performances. In chapters on the “boring parts” of Moby-Dick, the scandals that dogged the painter Thomas Eakins, the role of women in Andy Warhol's Factory films, “bad sex” and Tracey Emin's crudely evocative line drawings, and L.A. artist Vaginal Davis's pornographic parodies of Vanessa Beecroft's performances, Sex Objects challenges simplistic readings of sexualized art and instead investigates what such works can tell us about the nature of desire. In Sex Objects, Doyle offers a creative and original exploration of how and where art and sex connect, arguing that to proclaim a piece of art “about sex” reveals surprisingly little about the work, the artist, or the spectator. Deftly interweaving anecdotal and personal writing with critical, feminist, and queer theory, she reimagines the relationship between sex and art in order to better understand how the two meet-and why it matters.
Keywords: approches et analyses; art contemporain; arts; corps; cours; discipline; féminisme pop; har4600; histoire de l'art; premier cycle; queer; sexualité; thématiques

Radical gestures: feminism and performance art in North America - Wark, Jayne (McGill-Queen's University Press, 2006)
Wark brings together a wide range of artists, including Lisa Steele, Martha Rosler, Lynda Benglis, Gillian Collyer, Margaret Dragu, and Sylvie Tourangeau, and provides detailed readings and viewings of individual pieces, many of which have not been studied in detail before. She reassesses assumptions about the generational and thematic characteristics of feminist art, placing feminist performance within the wider context of minimalism, conceptualism, land art, and happenings
Keywords: 1900-1999; 1960-1969; 1970-1979; 1980-1989; 1990-1999; 2000 à aujourd'hui; 2000-2009; amérique du nord; amériques; approches et analyses; art contemporain; art féministe; arts; corps; cours; discipline; femmes* artistes; féminisme pop; har4600; histoire de l'art; histoire et politique; militance; performance; premier cycle; périodes historiques; régions géographiques; thématiques

La chirurgie mammaire et l'esthétiquement correct : le sein et les médias - Le Louarn, S.; Le Louarn, C. (Annales de Chirurgie Plastique Esthétique, 2005)
Résumé Cet article discute en quoi les normes du sein esthétiquement correct, les caractéristiques physiologiques du sein, l'allongement de la durée de vie et les possibilités de la chirurgie esthétique influencent la demande de modification mammaire. Puis il examine comment le sujet des modifications mammaires est traité dans différents médias : presse écrite (notamment féminine), documentaires et spectacles de téléréalité. Il constate un paradoxe entre d'une part, un contexte social qui durcit des normes, encourage la quête du bien-être et la réalisation de soi et prône la tolérance et, d'autre part, la réalité d'un certain déni du droit des femmes à choisir leur apparence mammaire. L'article tente de décrypter les obstacles historiques, philosophiques, sociaux, religieux et idéologiques impliqués. Enfin, il propose une nouvelle grille de lecture du positionnement d'un individu par rapport à la chirurgie esthétique selon deux axes : le « Faire » et le « Dire ». Cette grille pourra aider le chirurgien plasticien à mieux décoder la demande de chaque patiente, pour mieux la satisfaire.
Keywords: 1900-1999; 1990-1999; 2000 à aujourd'hui; 2000-2009; approches et analyses; corps; corps féminin; cours; discipline; discours médiatique; esthétique; europe; france; féminisme pop; hétérosexisme; occident; premier cycle; périodes historiques; régions géographiques; santé; sciences humaines; soc2051; sociologie; systèmes d'oppressions; thématiques

Pornography, Women and Feminism: Between Pleasure and Politics - Ciclitira, Karen (Sexualities, 2004)
This article draws on a qualitative research study which set out to explore women’s experiences and views of pornography within the broader context of conflicting feminist positions on pornography. The research methodology posed an implicit criticism of the kind of ‘findings’ familiar from mainstream psychological research: semi-structured interviews were conducted with women from diverse backgrounds in the UK, and feminist theory and discourse analysis were used to inform interpretation of their accounts. Although the question of feminism was not explicitly raised by the interviewer, it emerged as a recurrent theme in interviews, with interviewees suggesting that the feminist anti-porn stance in particular has influenced their perspective on pornography. Their accounts show that women’s experiences are variegated, individual and complex, and that discourses of pornography and feminism may be negotiated in unpredictable ways.
Keywords: 2000 à aujourd'hui; 2000-2009; approches et analyses; cours; discipline; europe; féminisme pop; pornographie; premier cycle; psychologie; périodes historiques; recherche qualitative; ressource en ligne; royaume-uni; régions géographiques; sciences humaines; sex1911; sexualité; thématiques

Pornography embodied: from speech to sexual practice - Mason-Grant, Joan (Feminist constructions, 2004)
What does it mean to conceptualize pornography as a material practice rather than as speech? Mason-Grant argues that this idea, fundamental to the work of Andrea Dworkin and Catharine MacKinnon, has been obscured in legal wrangling and political polarization over their civil ordinance. Within the arena of legal argument, where the principle of free speech holds sway for progressive thinkers, their analysis of pornography is rendered, at worse, an apology for censorship and, at best, an argument about the social force of speech, rather than recognized as a fundamental challenge to the very idea of pornography as speech. In this book, Mason-Grant first shows how the persistent 'speech paradigm' inevitably obscures the innovative core of the Dworkin-MacKinnon critique of mainstream pornography. She then develops an alternative 'practice paradigm' that critically engages their analysis, capturing and extending its core insights about the role of pornography in sexual practice. Drawing on phenomenology of the lived body, this alternative paradigm provides a way of re-thinking how the pervasive use of mass-market heterosexual pornography contributes to the cultivation of an embodied and tacit sexual know-how that is subordinating, and raises important questions about alternative materials produced and used by sexual minorities. In her conclusion, Mason-Grant considers the implications of her analysis not for law, but for a critical pedagogy in youth sexuality education.
Keywords: approches et analyses; corps; cours; discipline; discours dominant; féminisme pop; hétérosexisme; militance; patriarcat; philosophie; phénoménologie; premier cycle; pédagogie; sciences humaines; sex1911; sexisme; sexualité; sofia; systèmes d'oppressions; thématiques

Catching a wave: reclaiming feminism for the 21st century - Dicker, Rory Cooke; Piepmeier, Alison (Northeastern University Press, 2003)
Young women today have benefited from the strides made by grassroots social activists in the 1960s and 1970s, yet they are hesitant to identify themselves as feminists and seem apathetic about carrying the torch of older generations to redress persistent sexism and gender-based barriers. Contesting the notion that we are in a post-feminist age, this collection of essays identifies a third wave of feminism. The contributors argue that the next generation needs to develop a politicized, collective feminism that both builds on the strategies of second wave feminists and is grounded in the material realities and culture of the 21st century. Organized into five sections which mirror the stages of consciousness-raising, the book looks at a broad range of perspectives on the diversity, complexity, multiplicity and playfulness of the third wave. It is also a call to action for new voices to redefine a feminism that is not only personally aware, but also politically involved. (source: Nielsen Book Data)
Keywords: 2000 à aujourd'hui; 2000-2009; LGBTQIA2+; approches et analyses; cours; féminisme pop; militance; premier cycle; périodes historiques; soc2014; thématiques; transféminisme; troisième vague

The trouble with nature: sex in science and popular culture - Lancaster, Roger N. (University of California Press, 2003)
Roger N. Lancaster provides the definitive rebuttal of evolutionary just-so stories about men, women, and the nature of desire in this spirited expose of the heterosexual fables that pervade popular culture, from prime-time sitcoms to scientific theories about the so-called gay gene.
Keywords: LGBTQIA2+; anthropologie; approches et analyses; cours; discipline; féminisme pop; genre; identités LGBTQIA2+; lit4700; premier cycle; queer; ressource en ligne; sciences humaines; sexualité; soc2014; thématiques; études culturelles

"You Can Never Be Too Rich or Too Thin": Popular and Consumer Culture and the Americanization of Asian American Girls and Young Women - Lee, Stacey J.; Vaught, Sabina (The Journal of Negro Education, 2003)
First- and second-generation youth of color are vulnerable to racialized images of gender and sexuality as reflected in and perpetuated by dominant forms of popular and consumer cultures. These popular images inform the process of Americanization, including racialized sexualization, for first- and second-generation Americans. This paper examines the way first- and second-generation Asian American girls and young women interpret and reinterpret popular representations of their positions in the United States. Data from two qualitative studies on Asian American young women will be presented.
Keywords: 2000 à aujourd'hui; 2000-2009; amériques; approches et analyses; asie; corps; cours; discipline; féminisme pop; hmong; intersectionnalité; laos; premier cycle; périodes historiques; racisme; représentation des femme*; représentation des femmes* racisées; ressource en ligne; régions géographiques; sciences de l'éducation; sex2283; sexisme; systèmes d'oppressions; thématiques; états-unis

Carnal appetites: food, sex, identities - Probyn, Elspeth (Routledge, 2000)
n Carnal Appetites, Elspeth Probyn charts the explosion of interest in food - from the cults that spring up around celebrity chefs, to our love/hate relationship with fast food, our fetishization of food and sex, and the impact of our modes of consumption on our identities. 'You are what you eat' the saying goes, but is the tenet truer than ever? As the range of food options proliferates in the West, our food choices become inextricably linked with our lives and lifestyles. Probyn also tackles issues that trouble society, asking questions about the nature of appetite, desire, greed and pleasure, and shedding light on subjects including: fast food, vegetarianism, food sex, cannibalism, forced feeding, and fat politics.
Keywords: approches et analyses; care; corps; cours; discipline; féminisme pop; lit4700; premier cycle; ressource en ligne; sciences humaines; sciences sociales; sexualité; thématiques; études de genres